Comparison of Laminar, RNG, and LES Model for Wave Propagation Simulation with FLOW-3D - Yuniardi, Rizaldi; Istiyanto, Dinar Catur; Wulandari, Ika; Harita, Yofan Tahamano Deo; Firmansyah, Raka; Rachman, Reno Arief (UIR PRESS, 2025)
Understanding wave transformation and its interaction with coastal structures is critical for shoreline protection and design. While physical modeling has traditionally supported such studies, its high cost has led to increased reliance on numerical modeling. This study uses FLOW-3D to simulate wave propagation in a scaled 2D coastal wave channel and compares the performance of three turbulence models: Laminar, Renormalized Group (RNG) k-ε, and Large Eddy Simulation (LES). Simulations are based on a 3-meter wave height, 12-second period, and 7-meter water depth, with wave elevation recorded at six probes along the domain. Results show that the LES model achieved the most accurate prediction, with a significant wave height of 3.01 meters at the structure location—an error of only 0.33%—outperforming RNG and laminar models. These findings highlight the superior turbulence resolution of LES in capturing energy dissipation and wave evolution. The study provides practical guidance for coastal engineers in selecting turbulence models based on accuracy and computational trade-offs. Future research should include model validation with experimental or field data and extend to irregular wave conditions to enhance real-world applicability.